A study on modulation techniques for 5g / Liow Chee Shing - Liow , Chee Shing (2018)
The 5th generation of mobile communication network, or commonly known as 5G, is expected to be deployed sometime around year 2020. Ever since the first generation of mobile communication was deployed in 1980s, the demand of bandwidth has never been enough. In 5G, we are expecting more new devices to be integrated in the network due to the convenient of wireless and mobility to allow the devices easily connected to the internet, anywhere, anytime. These devices include smart devices, sensors, and even machines and vehicles. One way to satisfy the 5G requirements is by enhancing the modulation techniques. In 4G, OFDM is use as the multiplexing technique. OFDM has been known to increase the network capacity tremendously, but it has some drawbacks as well, such as high out-of-band (OOB) emission that requires guard bands among the subcarriers. Consequently, the spectral efficiency decreases. A number of new multicarrier methods such as FBMC, F-OFDM and UFMC have been proposed to overcome OOB emission in OFDM. UFMC seem to be the best potential candidate for 5G. Similar to other methods, UFMC uses digital filter to reduce the OOB emission. Longer filter may reduce OOB emission, but long filter also increases the complexity of the system. In this study, we carry out simulation using Matlab to study the effect of filter length on the network performance. Our study shows that the filter length has no direct relationship corresponding to the performance parameters of BER, FER and throughput. This suggests the selection of filter length required optimization, instead.